EDUCATIONAL ENVIRONMENT AS A MEANS OF ORGANIZING LANGUAGE EDUCATION - Lyubov’ V. Mikhaleva; Ekaterina M. Kuznetsova (Высшее образование в России)
The article presents the interpretation of the concept of educational environment as a means of organizing a competency-oriented professional language education, in particular as a means of formation of the complex of cultural competencies. We define a number of specific characteristics of the educational environment at a modern university, and in particularat a university or department of foreign languages.